Diagnostic value of tissue monensin concentrations in horses following toxicosis. (May 2014) - Bautista, Adrienne C.; Tahara, John; Mete, Aslı; Gaskill, Cynthia L.; Bryant, Uneeda K.; Puschner, Birgit
Two separate incidents of monensin exposure in horses resulting in toxicosis provided insight into the diagnostic value and interpretive criteria of various biological samples. In case 1, 25 horses broke into a shed and ingested feed that was supplemented with 800 g/ton (880 µg/g) of monensin. Within 48 hr, 1 horse had died, 2 developed cardiac arrhythmias, lethargy, and recumbency, and another was euthanized due to severe deterioration. Minimal histologic lesions were noted in the horse that died peracutely, while another showed characteristic lesions of acute cardiomyocyte degeneration and necrosis. Stomach content, heart, liver, urine, and serum revealed various detectable concentrations of monensin in clinically affected and unaffected horses with known exposure. In case 2, a pastured horse had access to a mineral mix containing 1, 600 g/ton (1, 760 µg/g) of monensin. Within 48 hr, the horse became symptomatic and was euthanized because of severe respiratory distress. Histologic cardiac lesions were minimal but detectable amounts of monensin were found in blood, heart, liver, and stomach contents. In both cases, monensin toxicosis was confirmed with toxicological analysis. These cases demonstrate an overall lack of correlation of monensin concentrations in various biological samples with clinical outcome. However, serum, urine, blood, liver, heart, and stomach content can be tested to confirm exposure. More importantly, the consistently higher concentrations found in heart tissue suggest this is the most useful diagnostic specimen for postmortem confirmation of toxicosis in horses especially in cases in which associated feed cannot be tested for monensin or in cases with no histologic lesions.